Total Recall: Intestinal TRM Cells in Health and Disease - Paap, Eva-Maria; Müller, Tanja M.; Sommer, Katrin; Neurath, Markus F.; Zundler, Sebastian (Frontiers in Immunology, 2021)
Tissue-resident memory T cells (TRM cells) have crucial functions in host defense in mucosal tissues. They provide local adaptive immune surveillance and allow the fast initiation of targeted adaptive immune responses in case of antigen re-exposure. Recently, an aberrant activation in the case of immunologically mediated diseases has been increasingly acknowledged. As the organ with the largest interface to the environment, the gastrointestinal tract faces billions of antigens every day. Tightly balanced processes are necessary to ensure tolerance towards non-hazardous antigens, but to set up a powerful immune response against potentially dangerous ones. In this complex nexus of immune cells and their mediators, TRM cells play a central role and have been shown to promote both physiological and pathological events. In this review, we will summarize the current knowledge on the homeostatic functions of TRM cells and delineate their implication in infection control in the gut. Moreover, we will outline their commitment in immune dysregulation in gastrointestinal auto-inflammatory and chronic inflammatory conditions and shed light on TRM cells as current and potential future therapeutic targets.